S12 The liverpool healthy lung project (lhlp) – seeking out lung disease. (15th November 2017) - Ledson, MJ; Grundy, S; Arvanitis, R; Timoney, M; Gaynor, E; Field, J
Abstract : Introduction: Liverpool has high respiratory morbidity with double the national lung cancer incidence, particularly in lower socioeconomic groups. To tackle this health inequality Liverpool CCG with the primary and secondary care sectors, Public Health and Liverpool University commenced a 3 year LHLP. The project cost £600 k in the first year. It was adopted by the national ACE program, and we report the first year results. Methods: Firstly, a series of coordinated focused public engagement events are arranged in areas with a high lung cancer incidence, aiming to promote positive messages around lung health, and address the fear and fatalism surrounding lung cancer, called 'Healthy Lung Events' Secondly, from GP records all aged 58–70 with COPD, who smoke, or have asbestos exposure are invited to a face to face lung health check by a respiratory nurse who promotes positive lifestyle messages and calculates a 5 year personal lung cancer risk through www.MyLungRisk.org and those >5% threshold are offered a low dose CT scan. Results: The 87 healthy lung events attracted 1943 interactions and 813 completed spirometry of which 146 (18%) were abnormal, triggering a primary care consultation. 2911 (40%) of 7274 eligible individuals attended the lung health check, where 1107 (38%) were offered a CT scan: of 1064 performed, 414 (39%) were abnormal (102 [9.6%] lung nodules and 17 [1.6%] lung cancer (65% resected). 726 (44%) of the 1658 (57%) without previously diagnosed COPD had abnormal spirometry. Based on the first year LHLP evaluation we have extended the eligible age range to 75 years, altered patient letters, and introduced a phone contact. Conclusions: This innovative project has improved access to respiratory healthcare in a deprived area of Liverpool, identified new COPD patients, and should improve outcomes for lung cancer in this disadvantaged population.